2017
DOI: 10.1016/j.antiviral.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Tracking HCV protease population diversity during transmission and susceptibility of founder populations to antiviral therapy

Abstract: Due to the highly restricted species-tropism of Hepatitis C virus (HCV) a limited number of animal models exist for pre-clinical evaluation of vaccines and antiviral compounds. The human-liver chimeric mouse model allows heterologous challenge with clinically relevant strains derived from patients. However, to date, the transmission and longitudinal evolution of founder viral populations in this model have not been characterized in-depth using state-of-the-art sequencing technologies. Focusing on NS3 protease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The evolvability of SARS-CoV-2 spike protein RBD in the presence of nAbs depends on both the mutation rate in the presence of selection pressure and the mutational tolerance of the spike protein. The mutation rate of SARS-CoV-2 is in line with that of other single-strand RNA viruses, [ 28 ], and is relatively high when compared against some members of this group (such as Hepatitis C) for which evolution has practical clinical consequences ( S1 Table ) [ 29 , 30 ]. Mutation rates themselves are evolvable and may increase over time due to natural selection [ 31 ].…”
Section: Discussionmentioning
confidence: 92%
“…The evolvability of SARS-CoV-2 spike protein RBD in the presence of nAbs depends on both the mutation rate in the presence of selection pressure and the mutational tolerance of the spike protein. The mutation rate of SARS-CoV-2 is in line with that of other single-strand RNA viruses, [ 28 ], and is relatively high when compared against some members of this group (such as Hepatitis C) for which evolution has practical clinical consequences ( S1 Table ) [ 29 , 30 ]. Mutation rates themselves are evolvable and may increase over time due to natural selection [ 31 ].…”
Section: Discussionmentioning
confidence: 92%
“…Mutation rates for RNA viruses in general are among the highest known (on the order of 10 −6 per base per viral replication cycle). When compared against many other RNA viruses, such as Hepatitis C, for which evolution has practical clinical consequences, SARS-CoV-2 has a relatively high evolutionary rate (Table S1) ( 32, 33 ). As mentioned earlier, the currently estimated mutation rate for SARS-CoV-2 is in the context of neutral genetic drift ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Next to chimpanzees, this human liver chimeric mouse model is also attractive for monitoring HCV drug resistance ( 118 ). Our laboratory has particular interest in this matter and showed that the combination of DAAs with entry inhibitors restricts the breakthrough of DAA-resistant viruses ( 119 , 120 ). Finally, the uPA-SCID mouse model is also applicable for studies concerning malaria, which is caused by the parasite Plasmodium falciparum , and the study of the hepatitis E virus (HEV) ( 121 125 ).…”
Section: Immunocompromised (Human) Liver Xenograft Mouse Modelsmentioning
confidence: 99%